شـعرية مابعد الحـداثـة (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Postmodernism – as a term and a critical and cultural theory – is still engulfed by much academic debate and semantic perplexity. It is true that some critics find it sufficient to consider it chronologically as a movement which appeared after modernism; however, the historical and theoretical circumstances that caused the demise of modernism and the rise of the emergent postmodernism are numerous. This paper seeks to delineate postmodernism as an expanding enterprise that incessantly dominates almost every aspect of the contemporary “global village”. Thus, the paper addresses the central attitudes and deliberations engendered by the term. It also highlights the problematic relationship between modernism and postmodernism. The “post-” syndrome is equally prioritised not only because of its morphological relevance, but because this epoch distinguishes itself by the culture of the “post-”. مايزال "مابعد الحداثة" – مصطلحاً و نظرية – محاطةً بالكثير من السجال الأكاديمي والغموض الدلالي. صحيح أن بعض النقاد ينظرون إليه من خلال موقعه الكرونولوجي ويعتبرون ظهوره بعد "الحداثة" مدخلاً كافياً لدراستها ولكن الظروف التاريخية والنظرية التي أدت إلى زوال "الحداثة" وانبثاق "مابعد الحداثة" متعددة جداً. فاختزال ظاهرة المعرفية إلى منظور أحادي تشويه للحقيقة. لذلك يحاول هذا البحث أن يؤطر "مابعد الحداثة" على أنه مفهوم آخذٌ بالسيطرة على معظم نواحي "القرية العالمية" المعاصرة. ويتناول البحث عدداً من المسائل الجدلية الدائرة حول "مابعد الحداثة" وحول العلاقة الإشكالية بينها وبين "الحداثة" مع التركيز على قضية "المابعد" ليس لأهميتها المورفولوجية فقط بل لأنها أسست لثقافة راهنة تدعى "المابعدية".